2017
DOI: 10.3171/2016.12.spine16756
|View full text |Cite
|
Sign up to set email alerts
|

Synovial cysts of the spine: long-term follow-up after surgical treatment of 141 cases in a single-center series and comprehensive literature review of 2900 degenerative spinal cysts

Abstract: OBJECTIVESynovial cysts of the spine are rare lesions, predominantly arising in the lumbar region. Despite their generally benign behavior, they can cause severe symptoms due to compression of neural structures in the spinal canal. Treatment strategies are still a matter of discussion. The authors performed a single-center survey and literature search focusing on long-term results after minimally invasive surgery.METHODS Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
62
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(64 citation statements)
references
References 98 publications
1
62
1
Order By: Relevance
“…Bruder et al analyzed 141 cases and reported a success rate of 94% with open resection through a hemi-laminectomy. In this series, there was a 7% recurrence and only 9% required spinal instrumentation on follow up 5) . A meta-analysis by Campbel et al reported clearly the superiority of open resection over percutaneous needle aspiration.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Bruder et al analyzed 141 cases and reported a success rate of 94% with open resection through a hemi-laminectomy. In this series, there was a 7% recurrence and only 9% required spinal instrumentation on follow up 5) . A meta-analysis by Campbel et al reported clearly the superiority of open resection over percutaneous needle aspiration.…”
Section: Discussionmentioning
confidence: 57%
“…Lumbar facet joint synovial cysts are rare lesions that may cause radiculopathy, neurogenic claudication and even cauda equina syndrome 2,[4][5][6][7] . The most frequent site where it is found is anterior to the yellow ligament, postero-lateral to the dura and its contents, at the L4-5 level [4][5][6] . It does not respond well to clinical management, oftentimes requiring surgical intervention.…”
Section: Introductionmentioning
confidence: 99%
“…They have a variable prevalence that goes from 1% in CT studies to a 2.2% as a casual finding during laminectomies [ 15 ], and to a 6.5% in MRI studies, being symptomatic in approximately half of the cases [ 2 ]. Even though they have a controversial origin [ 16 ], the most accepted theory is that it is a complex early disc degeneration process, with a pressure increase and facet hypertrophy associated with degenerative spondylolisthesis, which shows the role of instability in the development of facet joint cysts [ 1 ], being responsible for the symptoms [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is a plethora of different treatment strategies for the management of lumbar spine synovial cysts. However, total cyst excision via small flavectomy as the least invasive approach should be considered surgical therapy of choice 13,[21][22][23] . Spinal fusion is also considered an option when spinal instability is concerned to avoid cyst recurrence 10 .…”
Section: Discussionmentioning
confidence: 99%